2010
DOI: 10.4314/ijbcs.v4i2.58140
|View full text |Cite
|
Sign up to set email alerts
|

Saponins are involved in the analgesic and anti-inflammatory properties of <i>Ficus platyphylla</i> stem bark

Abstract: The analgesic and anti-inflammatory properties of saponins (FPS) from the methanol extract of Ficus platyphylla stem bark were studied in rodents. FPS significantly attenuated acetic acid-induced writhes in mice and inhibited responses in both phases I & II of formalin-induced nociception. FPS demonstrated significant antinociceptive activity in Analgesy-meter model of nociception and significantly attenuated albumin-induced oedema in rats. Morphine significantly (p<0.05) inhibited responses in both phases I &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…Prostaglandins are involved in pain perception; therefore, agents that inhibit their synthesis are possible remedies for pain. Several studies have also revealed that alkaloids, saponins and terpenoids do possess antinociceptive properties [34,[40][41][42] The present study therefore suggests that the antinociceptive effect of the methanolic bark extracts of T. brownii could be due to the activity flavonoids, alkaloids, terpenoids and saponins that have been confirmed to be present in this medicinal plant. One limitation of this study is that biochemical tests were not conducted to determine the effects of the methanolic bark extract of T. brownii on internal organs like the liver and the kidney.…”
Section: Discussionmentioning
confidence: 66%
“…Prostaglandins are involved in pain perception; therefore, agents that inhibit their synthesis are possible remedies for pain. Several studies have also revealed that alkaloids, saponins and terpenoids do possess antinociceptive properties [34,[40][41][42] The present study therefore suggests that the antinociceptive effect of the methanolic bark extracts of T. brownii could be due to the activity flavonoids, alkaloids, terpenoids and saponins that have been confirmed to be present in this medicinal plant. One limitation of this study is that biochemical tests were not conducted to determine the effects of the methanolic bark extract of T. brownii on internal organs like the liver and the kidney.…”
Section: Discussionmentioning
confidence: 66%
“…Bioactive compounds such as flavonoids, alkaloids, saponins, phenols, and cardiac glycosides found in the extracts have been found to possess analgesic and anti-inflammatory properties in previous studies. Numerous studies have shown that alkaloids possess analgesic and anti-inflammatory properties [29,30]. Flavonoids also show analgesic and anti-inflammatory activity by inhibiting prostaglandin synthetase, which in turn reduces prostaglandin synthesis and release [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Since flavonoids, saponins and tannins are important secondary metabolites of NNF and have exhibited inhibitory effects on arachidonic acid metabolism and prostaglandin synthesis [38][39][40]. Therefore the results of the tail flick test and acetic acid induced writhing test strongly recommend that the mechanism of the analgesic effect of NNF is connected with the blockade of arachidonic acid metabolism and inhibition of prostaglandin synthesis.…”
Section: Discussionmentioning
confidence: 99%